Successful professional reviews for civil engineering technicians : theoretical foundations and practical applications - Peake, Malcolm, active 2025 (Emerald Publishing Limited, 2025)
Successful Professional Reviews for Civil Engineering Technicians is the ultimate guide for any aspiring technicians or apprentices due to undertake the ICE Technician Professional Review (TPR) or End Point Assessment (EPA). Written for technicians by technicians, this book offers a complete understanding of the methodology involved for a successful professional review or end point assessment. It defines the basic knowledge, and the breadth of understanding required including numerous examples and anecdotes and shows how any candidate, from any background, might put together their application and prepare for the review/assessment. Written in plain English and peppered with hints, tips and examples, this title covers who are technicians; selecting a mentor and sponsor; key attributes of EngTech; putting your submission together what the whole review process is like; apprenticeships and the end point assessment. Successful Professional Reviews for Civil Engineering Technicians is an invaluable resource for technicians preparing for a TPR or EPA and their mentors wishing to understand the process more clearly.